Obtaining and Immunologic Characterization of Filoviruses Recombinant Proteins VP40 and NP - A. V. Ivanova; E. I. Kazachinskaya; A. V. Kachko; E. L. Subbotina; A. V. Sorokin; I. A. Razumov; S. V. Neteosov; V. B. Loktev (Проблемы особо опасных инфекций, 2010)
Full-size genes coding matrix proteins VP40 of Ebola virus (VE) and Marburg virus (VM) and nucleoprotein (NP) of VE were cloned. These genes expression in Escherichia coli and purification of their products by affinity chromatography using Ni-NTA agarose permitted to obtain full-size recombinant VP40 and NP proteins of filoviruses. Immunological studies showed the recombinant polypeptides to possess antigenic properties similar to those of the native viral proteins. These proteins can be used for constructing of experimental vaccines against filoviruses and improving immunodiagnostic tests against filoviral infections.